Intestinal Colonization Rate of Candida albicans among Low Birth Weight Neonates after Using Oral Synbiotic Supplementation: A Randomized Placebo-controlled Trial - Mazyar Vakiliamini; Homa Babaei; Maryam Mohammadi; Reza Habibi; Hajar Motamed (Mashhad University of Medical Sciences, 2020)
Background: The present study aimed to evaluate the effect of synbiotics on the intestinal colonization rate of Candida albicans in low birth weight neonates (i.e., under 2,500 g), which is one of the most important events for necrotizing enterocolitis (NEC). Methods: During one year, 106 preterm neonates with a birth weight of less than 2,500 g, admitted to the Neonatal Intensive Care Unit (NICU) of Imam Reza Hospital, affiliated to Kermanshah University of Medical Sciences, Kermanshah, Iran, were randomly selected and investigated in two groups of case and control. In the case group, 5 drops of synbiotics (under the trade name of Pedilact in which 5 drops are equivalent to 2.5×108 CFU), containing three probiotics of Bifidobacterium infantis, Lactobacillus rhamnosus, and Lactobacillus reuteri, as well as the prebiotic of fructooligosaccharide, were administered. On the other hand, 5 drops of distilled water were used for the control group. In the present single-blind study, the subjects were divided into two groups using a random number table. The stool cultures were obtained on the 1st and 10th days of admission. Then, the two groups were compared in terms of the amount of positive stool culture for Candida albicans, time of feeding initiation and full nutrition, duration of hospitalization, and time of discharge. Results: The incidence rate of positive stool culture for Candida albicans was 6.6%. A significant relationship was observed between gestational age and positive culture (P=0.009). However, there was no significant difference between the two groups in terms of the duration of hospitalization, time of feeding initiation and full feeding, good physical examination results, and wellbeing. In addition, the relationship between positive culture and birth weight was statistically significant (P=0.045) since the rates of positive culture were 57.1% and 42.9% in cases with the birth weight of ≤ 1,500 and > 1,500 g, respectively. Conclusion: Based on the results, synbiotic use showed no significant relationship with enteral positive cultures for Candida albicans, time of enteral feeding initiation and full feeding, and hospitalization duration.